Effects of added synthetic amino acids, with decreasing amounts of fat, on growth performance of growing pigs - R O Gottlob; Michael D Tokach; Robert D Goodband; Joel M DeRouchey; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2005)
A total of 1,210 growing gilts (initially 102.4 lb, PIC) were used in a 28-day study in a commercial research facility to determine the effects of added synthetic amino acids, with decreasing amounts of fat, on growth performance of growing pigs. Pigs were fed one of four experimental diets based on cornsoybean meal: 1) control (3% added fat, no synthetic amino acids), 2) 2.38% added fat and high concentrations of synthetic amino acids; 3) 1.90% added fat and high concentrations of synthetic amino acids, and 4) 1.43% added fat and high concentrations of synthetic amino acids. The amounts of added fat were chosen to equalize the energy content of the diet, according to a modified ME basis, with the ME value of soybean meal being set at 95, 90, and 85% of the ME of corn in Treatments 2, 3, and 4, respectively. Overall (d 0 to 28), pigs fed diets containing high concentrations of synthetic amino acids tended to have decreased ADG (P<0.09) and poorer F/G (P<0.11) than those of pigs fed the control diet. Linear and quadratic trends for ADG, ADFI, and F/G, with decreasing amounts of added fat, were not significant. The results of this study indicate that decreasing the amount of added fat when high concentrations of synthetic amino acids are added to the diet causes a numerically reduced ADG and poorer F/G.; Swine Day, 2005, Kansas State University, Manhattan, KS, 2005
Keywords: Swine day; 2005; Summary Publication of Report of Progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 964; Kansas Agricultural Experiment Station contribution; no. 06-63-S; Added fat; Amino acids; Growing-finishing pig; Swine